1962
DOI: 10.1152/ajplegacy.1962.203.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Diencephalic placement of estradiol and sexual receptivity in the female rat

Abstract: Behavioral receptivity, as indicated by the presence of the lordosis reflex, could be elicited from spayed rats after implantation of estradiol in the medial-basal preoptic and anterior hypothalamic regions. Hormone implants elsewhere in the hypothalamus or blank tubing implants throughout the hypothalamus did not produce this effect. Subcutaneous implants were equally ineffective for producing behavioral receptivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
61
2

Year Published

1964
1964
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(70 citation statements)
references
References 0 publications
7
61
2
Order By: Relevance
“…The clearest differences were apparent in the ventromedial nucleus and preoptic area. Electrical or chemical stimulation of the ventromedial nucleus facilitates feminine sexual behavior (Lisk, 1962;Barfield and Chen, 1977;Pfaff and Sakuma, 1979), but does not alter masculine sexual behavior (Dorner et aI. , 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The clearest differences were apparent in the ventromedial nucleus and preoptic area. Electrical or chemical stimulation of the ventromedial nucleus facilitates feminine sexual behavior (Lisk, 1962;Barfield and Chen, 1977;Pfaff and Sakuma, 1979), but does not alter masculine sexual behavior (Dorner et aI. , 1968).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat [L is k , 1960], rabbit [D a v id s o n and S a w y e r , 1961] and hamster [L is k and F e r g u s o n , in press], estrogen acts at the same site, namely the median eminence, to inhibit ovulation. In contrast, the estrogen sensitive sites mediating sexual receptivity are located in the pre-optic area in the rat [Lisk, 1962], the premammillary nucleus in the rabbit [P a l k a and S a w y e r , 1966], and the anterior hypothalamic area -ven tral filiform nucleus in the hamster. The significance of this variation in the functional anatomy of the hypothalamus is not known but may reflect the evolution of adaptations allowing each species to utilize different environmental and social cues to order their reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen consumption [Schiaffini and M a r in , 1971; M oguilevsky and M a l in o w , 1964], C 0 2 production [Sacchi et al, 1973], succinic dehy drogenase [M oguilevsky et al, 1964], cyctochrome oxidase [M oguilevsky et al, 1971], lactic dehydrogenase [M o rishita et al, 1972] and glucose-6-phosphate dehydrogenase [H u n t er and H a g y , 1969] are elevated during the estrous phase of the cycle. The metabolic changes we have observed in the present study occur in hypothalamic nuclei which have been shown to control ovulation and sexual behavior in electrical stimulation [Teresawa and Saw y e r , 1969], lesion production [A verill and P urves, 1963;Bishop et al, 1972;C arrer et al, 1973/74 [Lisk, 1962[Lisk, ,1967 or L H -R H localization [K in g et al, 1975;Palkovitsc/ o/., 1974;W heaton et al, 1975] experiments. The exact relationship between these metabolic events and the hormone release and sexual behavior has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 83%